(3GeJKGd GdCeQ aj bQGAI CHj YeQhs - (3YHO GdhgGH Hf CMeO Hf hgHGf GdMGQKj GdOeTbj, Cejf GdOjf,J (B768 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hSde JSdjekG cKjQkG GNQL GdGeGe CMeO GdKGfi hGdJQePi s
(3BNQgG (B:s
(3JMbbJ GdPi bO PcQJg JHhA HZQV ai GdbQGAIJeJ s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B180 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B220s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs